NEED ASSESSTMENT KURIKULUM KESEHATAN REPRODUKSI DI SMA KOTA SEMARANG - Agung Febri Nugroho; Eti Rimawati; Sri Andarini Indreswari (Dian Nuswantoro Semarang, 2011)
Background:The high demand of adolescents to information about sexual and reproductive health can be seen from the data in PILAR IPPA Central Java to March 2008 which recorded the 7810 partners have been consulted, with the demand for reproductive health information as much as 1335 with the percentage of high school level are 42.9%. School is an institution that conveys information about sex and reproductive health is good and right. Therefore important to describe how the needs of reproductive curriculum in senior high school level in Semarang City.Method: This type of research is a qualitative research by using case study approach. The tecnical sampling used purposive sampling which the respondent is headmaster of senior high school, while data collection is done through in-depth interviews with the variables based on the theory of Health Belief Model.Results: The number of respondents was obtained as many as 3 people and 3 informants crosscheck, namely students, parents, and the curriculum staff in nasional educationdepartement. All respondents are male. All the respondents held that the students as adolescents are vulnerable to reproductive health problems due to the condition of students who are still in transition (perceived susceptibility), and argues that the problem of unwanted pregnancy, abortion, STDs, and drugs as a form of adolescent reproductive health issues of concern andrequire attention (perceived seriousness). The benefits of reproductive health curriculum are considered to broaden the horizon of students and half of the respondents view to reduce reproductive health-related cases (perceived benefits). However, the provision of reproductivehealth materials in the schools hindered by the lack of policy from the national Education Department related to this issue, in addition to school still considers that the provision of reproductive health materials should be performed by experts (perceived barrier). The existence ofthe mass media can provide unlimited information and can be easily accessed by students need to require the attention of all parties, including parents and this is a factor driving the need for provision of reproductive health materials in schools (cues).The recommended advice is the formulation of policies governing the provision of reproductive health materials in senior high school needed and courage cooperation between government and private agencies in the provision of reproductive health materials at school.Keywords: Reproductive Health, Curriculum